Improved Preservation of Fresh Osteochondral Allografts for Clinical Use - Stoker, Aaron; Garrity, Joeseph T.; Hung, Clark T.; Stannard, James P.; Cook, Jimi (The Journal of Knee Surgery, 2012)
Introduction Fresh osteochondral allografts (OCAs) have been used clinically to treat cartilage focal defects of the knee for over 30 years. Over the last decade, significant research has been performed to develop and improve protocols for preservation of osteochondral tissue before transplantation into patients for treatment of cartilage defects. This work has resulted in preservation protocols that allow for maintenance of OCA tissues for time periods sufficient for clinical use based on disease testing requirements in the United States. However, graft quality and the window for clinical use of these tissues could be greatly enhanced from current levels.Materials and Methods Femoral condyles from 14 dogs were harvested and stored in one of the three proprietary media composition (M-1, M-2, M-3) and container condition (C-1, C-2, C-3) at 25°C for 63 days. Viability of the OCA was determined using a proprietary media metabolic assay and live cell fluorescent microscopy. Media biomarker concentrations were analyzed to determine the metabolic activity of tissue.Results Media protein biomarkers were detected throughout the culture period, indicating OCAs remain metabolically active at 25°C, and biomarker levels correlated with tissue viability. Viable chondrocyte density was maintained at day 0 levels throughout the depth of the tissue in the M-3 media using container condition C-3 after 63 days in storage. The media metabolic assay correlated strongly to cell viability of the OCA tissue.Conclusion These data indicate that near day 0 tissue viability can be maintained for up to 63 days when OCAs are stored at 25°C in the correct conditions. Further, tissue viability could be assessed nondestructively using media biomarkers and the media metabolic assay. If the preservation protocol reported here can be validated for safety and functional outcome, it could then be employed in tissue banks throughout the world, decreasing the number of grafts discarded and improving quality of life for thousands of patients affected by cartilage defects.
Keywords: osteochondral allograft; osteoarthritis; storage; viability